Estetika Tari Piriang Rantak Kudo di Sanggar Kuranji Sejati Kelurahan Kuranji Kecamatan Kuranji Kota Padang - Zeri, Syifa Oktawia; Asriati, Afifah (TSAQOFAH, 2025)
This study aims to explore and describe the aesthetic values of Tari Piriang Rantak Kudo, a traditional dance developed at Sanggar Kuranji Sejati, located in Kuranji Subdistrict, Padang City. The research is grounded in the importance of preserving traditional performing arts that are rich in cultural meaning and local aesthetic values. A descriptive qualitative method was employed, with the researcher serving as the main instrument, supported by writing tools and a camera. Data were collected through observation, interviews, and documentation, and analyzed through the stages of data collection, reduction, presentation, and verification. The findings reveal that the aesthetic value of Tari Piriang Rantak Kudo is reflected in three main aspects: form, substance, and performance. The form includes movement sequences such as masuk, sambah, manatiang piriang, and maangin, as well as linear and curved floor patterns. The dance is performed by two female dancers accompanied by traditional saluang pauh and gandang katindik music, using props such as plates and a proscenium stage. The substance aspect encompasses atmosphere, ideas, and symbolism (ibarat), while performance includes dancers’ talent, technical skills, and media support. These three aspects collectively form a distinctive aesthetic value that enriches the Minangkabau cultural heritage through meaningful traditional dance expression.